PENERAPAN MOTODE DRILL UNTUKMENINGKATKAN KETERAMPILAN MEMBUAT BENDA KONSTRUKSI SISWA KELAS IVSD NEGERI 145 PEKANBARU - Yanti, Helmi Yanti; Antosa, Zariul Antosa; Alpusari, Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Problems inthis studyis the low of valuethe skillsSBK for fourth grade students at SDN 145 Pekanbaru.For that we need to be improved in order to improve student’s skills. The efforts to repair by apply the drill method. This research is classroom action research. This research was conducted on fourth grade students at SDN 145 Pekanbaru academic year 2013/2014. Time of the research was conducted on 14 April 2014 until 29 Mei 2014. Subject of the research is fourth grade students at SDN 145 Pekanbaru which contains of 17 men and 19 women. Data collection techniqueswere used thatobservation techniquesandtrainingtechniques. Data analysis techniqueused isthe activities of teachersandstudents. From the value ofthe processand final valueof skill to themake constructionobjects. The result showed that the averagescore of studentswas59.31, has an increased on first cycle to 67.85. On the second cycle, the average score was 77.50, has an increased from basic score. From the explanation above showsthat theapplication of thedrillmethodcanincrease theskill of creatingobject construction on fourth grade students at SDN 145Pekanbaru. Key Word :Drill Method, SkillsMakeConstructionObjects